A strategic plan for Cyrgel Enterprises - Gonzales, Lani S.; Soledad, Miguel D.; Concepcion, Sylvia B. (Davao City School of Management, University of the Philippines Mindanao, 2010)
CYRGEL ENTERPRISES is a sole proprietorship which ventured in the world of business industrial competition. It started from preventive maintenance chemicals then later diversified its products into various industrial parts, and eventually into mechanical contracting works and services. The company is holding its office at Virsare Village, National Highway, Bago Aplaya, Davao City. CYRGEL ENTERPRISES is a trading company under the category of General Merchandise which focus on items needed by industrial companies like, Maintenance Chemicals, Industrial parts for Filler machines and Bottle Washer equipment of Coca-Cola Company. The company was able to acquire one unit of truck for hauling services at Coca-Cola Davao in October 2007 up to the present and at the same time a third party service provider of manual bottle washing activity which is done in the vicinity of the Coca-Cola Plant and in Cosmos Bottling Plant area. Aside from its existing industrial products, the organic products are additional product lines which are at present being developed in the market by the company with the Technical support of the Bioorganics Philippines, Incorporated. The strategic direction of the company now is to position the organic products in the industry since the usual practice of the industrial firms in treating their waste water is through the conventional use of chemicals. This is the challenge for Cyrgel on how to push the biological treatment and at the same time introduce the product to public sectors and neighboring communities. The main goal of the company, as envisioned by the owner, is to be known as the organic supplier company in the industry and the second principal products of distribution are the industrial supplies with mechanical/structural contracting works and services.
Thesis (Master in Management)--University of the Philippines Mindanao, April 2010.